Shear response of deep precast/prestressed concrete hollow core slabs subjected to fire - Nguyen, Hang T. N. (2022)
This paper presents experimental and numerical investigations on shear behavior of deep precast/prestressed concrete hollow core (PCHC) slabs under fire conditions. Five fire tests including one heat transfer (subjected to ISO 834 fire) and four structural shear tests (subjected to a non-standard fire curve) were conducted. Data obtained from the experiments were used to investigate shear behavior of deep PCHC slabs in the event of fire and to verify two sequentially-coupled finite element (FE) models simulating thermal and structural responses of deep PCHC slabs subjected to shear and under fire conditions. The verified FE models were then employed to extend the existing experimental database. Fire resistance of the four PCHC specimens subjected to ISO 834 fire was numerically obtained. It was shown that although all the specimens were designed to sustain 2 h fire resistance following the prescriptive method in Eurocode 2, they failed at early stages and did not meet their designed fire resistance. In addition, web-shear resistance of the hollow-core units decreased as slab depth increased. Moreover, from the test results, it was evident that temperature-induced tensile stresses, rather than fire-induced degradation in strength and stiffness of concrete and strands, governed the web-shear resistance of deep PCHC units. Furthermore, load level has a critical effect on web-shear resistance of deep PCHC slabs. Last but not least, data from the experimental and numerical studies were used to validate the formula to calculate shear capacity of PCHC slabs under fire conditions in EN 1168:2005+A3:2011.